Republic of Kosovo : Request for Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Kosovo's economic performance has strengthened considerably, but structural deficiencies undermine export sector development and prospects for sustainable growth. The program seeks to restore fiscal sustainability and safeguard financial sector stability. Restoring fiscal sustainability requires strengthening the credibility of the budget process and improving tax administration. Decisive action is necessary to improve energy sector finances and halt the drain of fiscal resources. Good governance of the Pension and Savings Trust is essential. Financial strength of the banking sector is adequate, but crisis preparedness needs to be enhanced.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet